DESIGN AND IMPLEMENTATION OF LOW POWER VLSI DESIGN CIRCUITS USING CAD TOOLS - CHANDRASHEKAR, P.; VASA, SANDEEP KUMAR; DEEPA, K. (International Journal of Psychosocial Rehabilitation, 2018)
In this technology, an power densities is measuring into watts per square millimetre as a raises to alarm rates, power managements are become an importance aspects of nearly each categories of the designed & applications. Reduces the power consumptions & in excess of on chips power managements is the key challenging into deep sub-micron meters nodes as increases complex. Power managements required at a consider into extremely in the early hours designed stage. Too lower power methods will be employs at every each designed stages, for RTL (Register Transfer Level) and GDSII. These are review papers is described in the different strategy, methodology & power managements technique form lowpower VLSI circuit. In expectations challenged in that may be meets through designs as to designing lowpower higher performances circuit is also discuss. Stateof theart optimized into method at various abstractions level in those targeting designs to lowpower digitals VLSI circuit is verified.